The Matthean community according to the beginning of his gospel - F. P. Viljoen (Acta Theologica)
The social setting of the Gospel according to Matthew remains a much debated issue. The theory of a gentile setting with historical roots within Judaism was met with much opposition in recent times. The expression “the parting of the ways” as introduced by Dunn and popularised by Stanton effectively marks this discussion. However, the relation between the Christian community of Matthew and Judaism remains a much debated issue. Some studies have argued that the Matthean community was sectarian in nature, being in conflict with a larger Jewish social context. From the Gospel it is clear that there was a struggle between the Matthean community and local Jewish communities and leaders. This indicates a distance between a Jewish background and a gentile presence within the community. Matthew views the new People of God as distinct from the nation which rejected Jesus as their Messiah. Within the discussion with regard to the Matthean community, the great commission (Matt. 28:18-20) is often seen as the key to understanding the whole book and particularly the community. However, the importance of the beginning of the Gospel is often neglected in this discussion. In this article I attempt to show the importance of the opening narrative in defining this community.